ATENCIÓN A LOS USUARIOS EN LA CLÍNICA TOUMA - Vera Coello, Lissette del Carmen (2018)
The Clinic "Touma" with the purpose of serving the community in incomparable hospital services with technical experts and health specialists, being from the same city as Guayaquil, was created on June 3, 1989, and is located in the Canton Babahoyo Province Of Los Ríos In Las Calles Ricaurte 112 Between General Barona And Malecón And It Is Made Up Of 82 Employees